Answer to Question #21984 in Trigonometry for Kristen Woods
Simplifiy and solve
3. 30 square root of -25 * 8 sqaure root of -49
4. 6 square root of -64 + 12 square root of -36
5. 4 sqaure root of -13 - 6 square root of -13
1
2013-01-18T08:58:45-0500
3) 30 square root of -25 * 8 sqaure root of -49
30 * sqrt(-25) * 8 * sqrt(-49) =
= 30 * 5i * 8 *7i
= (30 * 5 * 8 *7) * (i*i)
= 8400 * (-1)
= -8400
-------------------------------------------------------
4) 6 square root of -64 + 12 square root of -36
6 * sqrt(-64) + 12 * sqrt(-36) =
= 6 * 8i + 12 *6i
= 48i + 72i
120i
-------------------------------------------------------
5) 4 square root of -13 - 6 square root of -13
4*sqrt(-13) - 6*sqrt(-13)
= -2 *sqrt(-13)
= -2 sqrt(13) *i
Need a fast expert's response?
Submit order
and get a quick answer at the best price
for any assignment or question with DETAILED EXPLANATIONS!
Comments
Leave a comment